Step-by-step explanation:
6x - 3x^2 + 2x^2 -2x = 5x^2 + 15x
4x -x^2 = 5x^2 + 15x
-11x - 6x^2 = 0
-6x^2 - 11x = 0
use the quadratic formula
(-b±√(b²-4ac))/(2a)
Answer:
below( hope this helps )
Step-by-step explanation:
2. No because we don't know if the triangles are right triangles.
3. unknown since there are no labels to what the triangle points are
Answer:
Step-by-step explanation:
if we have a right triangle,
one angle=90
180-90=90
let x be one angle, and y another angle
the other is 2x+30
x+2x+30=90
3x=60
x=20
y=70
The answer to the selected problem is: that is a linear equation.
Answer:
<h2>0.64</h2>
Step-by-step explanation:
4.48/7
7 into 4 (0 times)
Bring next number down 4.48 ⬇️
7 into 44 (6 times, 2 left over)
Bring next number down 4.48 ⬇️
7 into 28 (4 times)
Answer 0.64
I'm always happy to help :)